Hubungan Perilaku Phubbing dan Komunikasi Interpersonal Mahasiswa Bimbingan dan Konseling Universitas Sriwijaya - Fitriana, Sindi; Dewi, Ratna Sari (Universitas Muhammadiyah Metro, 2025)
This study aims to determine the relationship between phubbing behavior and interpersonal communication in students of the Guidance and Counseling Study Program of Sriwijaya University. This study involved 366 students of the Guidance and Counseling Study Program of Sriwijaya University from the Indralaya and Palembang classes from 2021 to 2024, with a sample of 79 students obtained through the Slovin formula. The sampling technique applied was Probability Sampling with the Simple Random Sampling method. The research instrument consists of a phubbing behavior scale and an interpersonal communication scale, with data analysis using Pearson Product Moment correlation.The results of this study found that a significant negative relationship between phubbing behavior and interpersonal communication (r = -0.468, p < 0.05), which means that the higher the phubbing behavior, the lower the interpersonal communication skills of students. This finding shows the importance of building awareness in the wise use of technology so as not to reduce the quality of social interactions, especially in academic environments that highly demand good communication skills.